Dual Recognition Strategy for Specific and Sensitive Detection of Bacteria Using Aptamer-Coated Magnetic Beads and Antibiotic-Capped Gold Nanoclusters - Cheng, Dan; Yu, Mengqun; Fu, Fei; Han, Weiye; Li, Gan; Xie, Jianping; Song, Yang; Swihart, Mark T; Song, Erqun (Analytical chemistry (Washington), 2016)
Food poisoning and infectious diseases caused by pathogenic bacteria such as Staphylococcus aureus (SA) are serious public health concerns. A method of specific, sensitive, and rapid detection of such bacteria is essential and important. This study presents a strategy that combines aptamer and antibiotic-based dual recognition units with magnetic enrichment and fluorescent detection to achieve specific and sensitive quantification of SA in authentic specimens and in the presence of much higher concentrations of other bacteria. Aptamer-coated magnetic beads (Apt-MB) were employed for specific capture of SA. Vancomycin-stabilized fluorescent gold nanoclusters (AuNCs@Van) were prepared by a simple one-step process and used for sensitive quantification of SA in the range of 32–108 cfu/mL with the detection limit of 16 cfu/mL via a fluorescence intensity measurement. And using this strategy, about 70 cfu/mL of SA in complex samples (containing 3 × 108 cfu/mL of other different contaminated bacteria) could be successfully detected. In comparison to prior studies, the developed strategy here not only simplifies the preparation procedure of the fluorescent probes (AuNCs@Van) to a great extent but also could sensitively quantify SA in the presence of much higher concentrations of other bacteria directly with good accuracy. Moreover, the aptamer and antibiotic used in this strategy are much less expensive and widely available compared to common-used antibodies, making it cost-effective. This general aptamer- and antibiotic-based dual recognition strategy, combined with magnetic enrichment and fluorescent detection of trace bacteria, shows great potential application in monitoring bacterial food contamination and infectious diseases.